Applying System Dynamics to Evaluate Lean Manufacturing Interventions in a Traditional Bakery: A Case-based Conceptual Approach - Fredy Sumasto; Najla Aulia; Arif Setiadi; Fahriza Putra Zaman; Muhammad Raihan Adil; Febriza Imansuri; Indra Rizki Pratama; Dianasanti Salati; B. Handoko Purwojatmiko (Universitas Atma Jaya Yogyakarta, 2026)
Small and medium-sized enterprises (SMEs) in the traditional food sector often face operational inefficiencies caused by disorganized workspaces, inefficient layouts, and limited adoption of structured improvement practices. These challenges are particularly evident in small bakeries where manual production processes and spatial constraints disrupt workflow continuity. This study aims to analyze the relationships between operational inefficiencies and Lean Manufacturing interventions using a System Dynamics approach. A qualitative case study was conducted at Toko Roti Gelora, a traditional bakery in Jakarta, Indonesia. Data were collected through direct observation, informal interviews, and document analysis over a ten-week field study. Lean diagnostic tools, including Value Stream Mapping and Fishbone Diagram analysis, were employed to identify sources of operational waste. The findings were synthesized into a Causal Loop Diagram (CLD) to represent feedback structures influencing production efficiency. The results identify four key feedback loops shaping the bakery’s operations: two reinforcing loops representing the escalation of inefficiencies and the development of Lean culture, and two balancing loops representing system stabilization through 5S implementation and layout improvements. These interactions suggest how Lean interventions may contribute to reducing search time, motion waste, waiting time, and excess inventory while supporting the development of workplace discipline over time. The study contributes by integrating Lean Manufacturing and System Dynamics to propose a systemic framework for analyzing operational efficiency in SME production systems.